The model to calculate the radial velocities of fragments after PELE penetrator perforating a thin plate. (September 2016) - Fan, Zijian; Ran, Xianwen; Tang, Wenhui; Ke, Yuhong; Li, Zebin
Highlights: In the process of a PELE penetrator penetrating into a metallic thin plate, the deformation of the front part of PELE can be simplified into two phases: one-dimensional axial compression during penetration and radial free expansion during complete perforation. According to shock wave theory, it can be assumed that the kinetic energy of a PELE penetrator accumulates as compression energy in the first phase and is then completely released as the kinetic energy of fragments in the second phase. With this assumption, the scattering radial velocity of fragments after a PELE penetrator perforates a thin plate can be calculated. A comparison of experimental data for radial velocities obtained from various impact conditions with date calculated using the model presented here was consistent. Further analysis shows that the maximum radial velocity of fragments is tightly correlated with the bulk modulus and the Poisson's ratio of both the jacket and the filling of the PELE penetrator, and increase with an increase in both. For the same impact velocity, the radial velocities of the scattered fragments increase with an increase of both the thickness and the shock impedance of the target plate. Abstract: In the process of a PELE penetrator penetrating into a metallic thin plate, the deformation of the front part of PELE can be simplified into two phases: one-dimensional axial compression during penetration and radial free expansion during complete perforation. According to shock wave theory, it can be assumed that the kinetic energy of a PELE penetrator accumulates as compression energy in the first phase and is then completely released as the kinetic energy of fragments in the second phase. With this assumption, the scattering radial velocity of fragments after a PELE penetrator perforates a thin plate can be calculated. A comparison of experimental data for radial velocities obtained from various impact conditions with date calculated using the model presented here was consistent. Further analysis shows that the maximum radial velocity of fragments is tightly correlated with the bulk modulus and the Poisson's ratio of both the jacket and the filling of the PELE penetrator, and increase with an increase in both. For the same impact velocity, the radial velocities of the scattered fragments increase with an increase of both the thickness and the shock impedance of the target plate.